HOW SOCIAL MEDIA AND ONLINE REVIEWS AFFECT CUSTOMER TRUST AND WILLINGNESS TO PURCHASE HOSPITAL SERVICES - Miyazi, Hafizhah Nur; Masnita, Yolanda; Kurniawati, Kurniawati (Jurnal Manajemen Terapan dan Keuangan, 2026)
Abstract This study examines the effect of social media and online reviews on customer trust and willingness to buy healthcare services in Indonesia, with a focus on the effects of perceived utility, psychological risk, price, and time. A quantitative method was used with the Technology Acceptance Model (TAM) as a theoretical framework. Data were obtained from 187 respondents in JaBoDeTaBek using purposive sampling, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that price, time, perceived psychological risk, and customer trust have a substantial effect on willingness to acquire hospital services through digital platforms. Perceived usefulness has no significant effect on willingness to purchase hospital services through digital platforms. The model accounts for 89.4% of the variance in willingness to purchase, indicating a significant predictive ability. The results indicate that hospitals should focus on trust-building, providing timely service information, and handling psychological issues through strategic digital communication to promote customer involvement in the digital healthcare era  Keywords: Customer Trust, Willingness to Purchase, Perceived Usefulness, Perceived Psychological Risk.